Morphological characters of immature stages of Palaearctic species of Cleopomiarus and Miarus and their systematic value in Mecinini (Coleoptera, Curculionidae, Curculioninae) - Skuhrovec, Jiří; Gosik, Rafał; Caldara, Roberto; Toševski, Ivo; Łętowski, Jacek; Szwaj, Ewelina (ZooKeys, 2018)
The relationship between the genera Cleopomiarus and Miarus of Mecinini (Curculionidae, Curculioninae) was tested on the basis of morphological characters from the immature stages. The mature larvae of five Cleopomiarus species (C.distinctus (Boheman, 1845), C.graminis (Gyllenhal, 1813), C.longirostris (Gyllenhal, 1838), C.medius (Desbrochers des Loges, 1893), and C.meridionalis (H. Brisout de Barneville, 1863)), three Miarus species (M.abnormis Solari, 1947, M.ajugae (Herbst, 1795), and M.campanulae (Linnaeus, 1767)), and the pupae of four Cleopomiarus species (C.distinctus, C.graminis, C.longirostris, and C.medius) and two Miarus species (M.abnormis and M.ajugae) are described in detail for the first time. To confirm the taxonomic identification of some larvae, DNA COI barcode was obtained and compared with those of adults. The immature stages of the species herein studied were compared with those known from other genera in tribe Mecinini. It is suggested that Miarus and Cleopomiarus may be monophyletic based on several shared distinctive characters. Larvae of Miarus have a characteristic maxillary mala with six finger-like dms of two sizes (one or two dms very long and the rest of medium length), this feature being apparently unique among weevils. Other genus-specific character states are observed in the pupae, such as the length of setae on the head, rostrum and pronotum, including the number of rs on the rostrum, ds on pronotum, and finally the shape of the urogomphi. A key to the described larvae and pupae were respectively presented. New biological and distributional data on some species are reported.
Keywords: mature larva; Miarus; Cleopomiarus; biology; distribution; pupa; Mecinini; morphology